Fronto‐parietal and temporal brain dysfunction in depression: A fMRI investigation of auditory mismatch processing - Zweerings, Jana (Hum Brain Mapp, 2019)
Mismatch responses reflect neural mechanisms of early cognitive processing in the auditory domain. Disturbances of these mechanisms on multiple levels of neural processing may contribute to clinical symptoms in major depression (MD). A functional magnetic resonance imaging (fMRI) study was conducted to identify neurobiological foundations of altered mismatch processing in MD. Twenty‐five patients with major depression and 25 matched healthy individuals completed an auditory mismatch paradigm optimized for fMRI. Brain activity during mismatch processing was compared between groups. Moreover, seed‐based connectivity analyses investigated depression‐specific brain networks. In patients, mismatch processing was associated with reduced activation in the right auditory cortex as well as in a fronto‐parietal attention network. Moreover, functional coupling between the right auditory cortex and frontal areas was reduced in patients. Seed‐to voxel analysis on the whole‐brain level revealed reduced connectivity between the auditory cortex and the thalamus as well as posterior cingulate. The present study indicates deficits in sensory processing on the level of the auditory cortex in depression. Hyposensitivity in a fronto‐parietal network presumably reflects altered attention mechanisms in depression. The observed impairments may contribute to psychopathology by reducing the ability of the affected individuals to orient attention toward important environmental cues.